Experiential-role approach in psychotherapy - Gornostai, Pavlo (Psychological Counseling and Psychotherapy, 2022)
The article presents the author's approach to the practice of psychological help, which we call experiential-role psychotherapy. It comes into being as a synthesis of methods of psychodrama, transactional analysis, the theory of systemic family psychology and psychotherapy, and a problem approach to the practice of psychological help based on author’s practical achievements and theoretical models. The essence of the method is the organization of emotional experience and practical experience in a state of role impersonation. The method makes it possible to work with a wide variety of problem topics, situations, relationships. Among them, three directions can be distinguished that determine the specificity of psychotherapeutic interventions. The first direction covers interventions in a state of non-hypnotic age-related regression, using transactional models of redecision and reparenting. Such work allows solving many psychotherapeutic tasks: changing ineffective and destructive scripted beliefs, improving self-relationship, harmonizing relationships with others. The second direction includes interventions focused on experience of physical sensations; their goal is a redecision at the level of the bodily script. This work is aimed at problems related to bodility, including psychosomatic reactions, dysfunctions of individual organs and systems of the body, and even with psychosomatic diseases in the early stages of development. The third direction is interventions within the framework of the family system; here there is a redecision in the state of historical regression at the level of the family-generic script. The work uses the model of the family-ancestral unconscious and is aimed at solving a number of systemic problems related to problematic or traumatic family information, excluded figures, family secrets, etc. Special attention is paid to working with the consequences of collective traumas experienced by a person's relatives and ancestors. In addition to traditional role figures, the work uses specific “age-related”, “bodily” and “historical” roles, that opens up the possibility of successful psychotherapy in working with many problems.